(untitled) (Research, Society and Development, 2024)
The present study presents a literature review on omega-3 fatty acids and their impact on health and longevity. Due to the increased interest in health promotion and healthy aging, omega-3 fatty acids have gained a large role in society due to their diverse benefits. These acids, not synthesized by the body, are acquired from the diet and stand out for their anti-inflammatory, cardiovascular and neuroprotective effects, making them promising targets for nutritional interventions. The review analyzed 58 articles over the last 5 years, using the National Library of Medicine (PubMed) database. The results reveal that omega-3 is associated with a reduced risk of cardiovascular disease, with beneficial effects on blood pressure, triglycerides and endothelial function. Furthermore, they demonstrate powerful anti- inflammatory effects, even influencing conditions such as rheumatoid arthritis and cancer. In the nervous system, it stands out for its neuroprotective effects, related to the prevention of neurodegenerative diseases and cognitive improvement. Although benefits for bone health were observed, the review highlights the need for more research, recognizing limitations in studies such as heterogeneity in research methods. The direct relationship between omega-3 and longevity demands specific, long-term investigations. In conclusion, this article highlights omega-3 as a promising intervention for promoting health and increasing longevity, suggesting its inclusion in the diet, but highlighting the continued importance of research to consolidate these findings.